Revealing the protective and pathogenic potential of MAIT cells. (November 2018) - D'Souza, Criselle; Chen, Zhenjun; Corbett, Alexandra J.
Graphical abstract: Highlights: MAIT cells respond to vitamin B-based antigens. MR1 tetramers and mouse models have enabled recent advances in MAIT cell research. MAIT cells contribute to immune protection against a range of bacterial pathogens. MAIT cells contribute to pathology in chronic Helicobacter pylori infection. Signals driving MAIT cell protective vs pathogenic responses are yet to be defined. Abstract: Mucosal-associated Invariant T (MAIT) cells represent a large proportion of T cells in human blood, and are also present throughout the body, being concentrated at mucosal sites. Their high level of conservation throughout mammalian evolution and recognition of conserved microbial antigens, derived from precursors of riboflavin (vitamin B2) biosynthesis, suggest an important role in protective immunity to pathogens. However, the picture that is emerging of MAIT cell immune function is increasingly complex, with numerous correlations of MAIT cell numbers with human diseases, and with recent studies demonstrating their pathogenic potential. The conditions that drive MAIT cell responses towards a protective versus pathogenic role are only beginning to be deciphered and, yet, must be understood for any attempt to harness MAIT cells therapeutically. In this review we summarise our current knowledge of immune protection and pathology driven by MAIT cells, models used to study their role in immunity and steps towards elucidating the immune signals driving these responses.